Biogenic mineralization in the ferromanganese nodules and crusts from the South China Sea. (March 2019) - Jiang, Xiao-Dong; Sun, Xiao-Ming; Guan, Yao
Graphical abstract: Highlights: Fe-Mn nodules and crusts in the SCS contain abundant microfossils and bio-marks. Microorganisms may have served as seeds/templates and triggered mineral deposition in the nodules and crusts. Microorganism activities played a major role, and chemical oxidation had a minor contribute to the formation of the nodules and crusts. Abstract: Global marine ferromanganese (Fe-Mn) nodules and crusts host immense metal resources, and the metal enrichment mechanism is still in dispute. The South China Sea (SCS) is one of the largest marginal seas in the western Pacific, and its northern slope is a passive continental margin with high sedimentary rate. A large amount of ferromanganese nodules and crusts have been discovered in the SCS northern slope. Previous investigations shown that the SCS nodules/crusts are often smaller and thinner, and contain higher Si and Al but lower Mn, Co and Ni than the Western Pacific nodules and crusts. In this study, high resolution scanning electron microscope (HR-SEM) and energy dispersive spectrometer (EDS) were performed to explore the microorganism activities with respect to the nodules/crusts formation. Various biogenic signature and microfossils in the SCS Fe-Mn nodules/crusts are recorded. These bio-marks and microfossils present several morphological types: tubiform burrows, bulbiform organism fossils, mould structures, cylindrical protozoan, globular growth structures, isolated spheroidal bacteria and biofilms. These mineralized bio-marks and microfossils are mostly protozoans belonging to various bacteria, biofilm, diatoms and coccoliths with Mn and/or Fe on their surface. Using the electron probe micro analyzer (EPMA), the microfossil-rich areas contain higher Mn than the surrounding microfossil-poor areas are observed. The abundance of bio-marks and microfossils and their geochemical features support a dominant role of microorganism activities in the SCS nodule/crustal formation. We proposed that microorganisms may have served as seeds/templates to induce mineral deposition in the nodules and crusts, and chemical oxidation and other abiotic mechanisms also contribute to the Fe-Mn oxide formation. The biogenic hypothesis provides another perspective to further understand the formation of deep marine Fe-Mn nodules/crusts, and will be important for exploration of Fe and Mn metals in the future.